A new interpretation of the sedimentary cover in the western Siljan Ring area, central Sweden, based on seismic data - Juhlin, Christopher; Sturkell, E.; Ebbestad, J.; Lehnert, O.; Högström, A.; Meinhold, G. (2012)
Two new reflection seismic profiles over the Paleozoic successions of the western part of the Siljan Ring impact structure show a contrasting seismic signature. The more southerly c. 10. km long Mora profile reveals a highly disturbed structure, with only a few kilometers of relatively horizontally layered structures observed. However, interpretations of refracted arrivals in the data, that can be correlated to reflections, indicate the Silurian clastic rocks to be about 200. m thick in the central part of the profile. Weak reflections from about 600. m depth suggest a 400. m thick Ordovician limestone sequence to be present. Cores from the area show a mainly shale lithology for the Silurian and only a thin sequence of Ordovician strata, suggesting a rapid thickening of the Ordovician towards the north. On the more northern c. 12. km Orsa profile clear reflections from the Paleozoic successions are seen along the entire profile, except on the southernmost few kilometers. Based on interpretations of refracted arrivals, the Silurian succession appears to be considerably thinner here, and possibly absent at some locations. The Ordovician is also interpreted to be thinner in this area, with a maximum thickness of about 200-300. m along most of the profile. A deeper reflection from about 2. km within the crystalline basement may represent a dolerite sill. The lack of clear basement reflections on the Mora profile can be attributed to near-surface conditions and the acquisition geometry. The seismic data and recent coring in the area suggest the presence of a deeper paleo-basin towards the southwest with significantly more shales being deposited and the Paleozoic successions being severely disturbed. The shallow coring and seismic data will help form the basis for locating future boreholes for deeper drilling to study impact processes and the Paleozoic evolution of central Sweden.